Reactivation of Industrial Spent Hydrocracking Catalyst for Tetralin Selective Hydrogenation and Ring-Opening - Liu, Junhao; Geng, Xuchao; Ma, Wenshuo; Wang, Xiaohui; Hu, Yue; Fu, Jianye; Ma, Lishuang; Lyu, Yuchao; Liu, Xinmei (Industrial & engineering chemistry research, 2024)
Reactivation of industrial spent hydrocracking catalysts can reduce fresh catalyst consumption and hazardous waste emissions, generating significant economic and environmental benefits. However, seldom have reports on this subject been found. Herein, a solvent-induced coordinating method was developed to reactivate the industrial spent hydrocracking catalysts for tetralin selective hydrogenation and ring-opening to produce benzene, toluene, and xylene (BTX). The developed reactivation method could redisperse the aggregated Ni, Mo active phases and transform the inert β-NiMoO4 phases into the type II NiMoS active phases after sulfidation. The newly formed NiMoS active phases bear 2–3 stacking layers and short stacking lengths over the reactivated catalyst. Besides, the porous structure is reconstructed by removal of the framework aluminum (FAL) and the extra-framework aluminum (EFAL) from the support, and the acidity of the reactivated catalyst is enhanced by the introduction of Beta zeolite. Compared with the spent catalysts, the hydrocracking performance of the reactivated catalysts shows a significant improvement. The tetralin conversion is 83% with a BTX selectivity of 48%, which is comparable to the performance of the freshly prepared catalysts reported in the literature. This work provides a new idea for the resource utilization of spent hydrocracking catalysts.